Parent-Child Contact and Post-Separation Parenting Arrangements - Wolcott, I; Smyth, B (My University, 2004)
The report presents qualitative data from a series of ten focus groups which formed the Parent-Child Contact Study, a component of the larger Australian Institute of Family Studies Caring for Children after Parental Separation Project. Fifty-four separated or divorced parents took part in the focus group discussions about different aspects of parent-child contact. The qualitative data are also embedded in the wider national picture through an examination of data derived from a large representative sample of separated/divorced parents who participated in the Household, Income and Labour Dynamics in Australia (HILDA) survey.
Australian Institute of Faimly Studies Research Report
Research Reports
Keywords: Families -- Parents and Parenting; Families; Families and relationships; Families and relationships